Peran Pendidikan Kewarganegaraan dalam Mencegah Radikalisme di Kalangan Generasi Muda - Nurzelika Putri; Oktarina Berlianti; Lia Sulistiarini; Darma Wita; Fitria Rahmadina; Septia Tri Wahyuni; Mila Wilanda; Deffny Gusmalinda; Nelsi Mersadila; Hambali Hambali (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
Radicalism among the younger generation poses a serious threat to national unity, especially in the digital era that facilitates the spread of extremist ideologies. This study employs a descriptive qualitative method with literature review as the data collection technique to analyze the role of civic education in preventing radicalism. The findings show that civic education can shape character, instill values of tolerance, democracy, and nationalism, and enhance students’ critical thinking skills in filtering radical information. Its implication is that civic education plays a strategic role as an ideological shield, effectively protecting youth from radical influences and encouraging their active contribution to preserving national unity.